Multilingual Intermediate Task Integration for Robust Zero-Shot Cross-Lingual Transfer in XQuAD - Assignee Research (Assignee Research, 2026)
Pre-trained multilingual language encoders, such as multilingual BERT and XLM-R, show great potential for zero-shot cross-lingual transfer. However, these multilingual encoders do not precisely align words and phrases across languages. Especially, learning alignments in the multilingual embedding space usually requires sentence-level or word-level parallel corpora, which are expensive to be obtained for low-resource languages. An alternative is to make the multilingual encoders more robust; when
Machine-generated literature synthesis.